Passionflower and Sage for Mental Health - R Hajiaghaee; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2013)
Herbal medicines include a range of pharmacologically active compounds: in some cases it is not well understood which ingredients are important for a therapeutic effect. The supporters of herbal medicine believe that isolated ingredients in the majority of cases have weaker clinical effects than whole plant extract, a claim that would obviously require proof in each case. Generalizations about the efficacy of herbal medicines are clearly not possible. Each one needs systematic research including a variety of animal studies and also randomized clinical trials. In this review we focus on Passiflora incarnata and Salvia officinalis.